Sustainable wellbeing indicators for Malaysia an alternative to current Malaysia wellbeing indicators - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Wolters Kluwer, CCH Asia, 2016)
This study is a part of an ongoing research which aims to discover appropriate social indicators in determining the sustainable well-being of Malaysians. The indicators will serve as an alternative to the Malaysia Quality of Life Indicators (MQLI), published in 1999, 2002, 2004 and 2011, as well as the current Malaysia Well-being Indicators (MWI) published in 2013, developed by the Economic Planning Unit of Malaysia (EPU). This paper aims to highlight and discuss the issues observed from the government’s current approach in measuring the country’s quality of life and wellbeing. Additionally, potential solution will also be recommended. The MQLI and MWI gauge the commitment towards providing a holistic approach to an all-inclusive and a well-balanced development concentrating on all aspects of life which includes economic, social and psychological aspects. Indicators and components selected for every ensuing report have been ever-changing. EPU’s continuous efforts in gauging Malaysia well-being through regularly revised social indicators are commendable. Some of the indicators though in line with the commitment of the government to improve the well-being of Malaysia, but they hardly measure the outcome of the commitments. This paper further discussed the issues found in the Malaysia Quality of Life and Well-being Reports in an attempt to propose an alternative solution. The solution was drawn from Hierarchy of Needs that prioritise social development before pursuing other needs. The study anticipates that by recognising and fulfilling the hierarchy of needs of the citizens, sustainable well-being is attainable.